Influence of Concentration and Temperature on Stability of Imipenem Focused on Solutions for Extended Infusion - Chuleegone Sornsuvit (SAGE Publishing, 2021)
Background Imipenem remains active against most Gram-positive and Gram-negative organisms. This study aimed to evaluate chemical stability of imipenem in 2 commonly used concentrations when stored in 3 various temperatures. Methods Imipenem injection powder was used to prepare 5 mL and 10 mg/mL of imipenem in .9% sodium chloride solution. Prepared solutions in PVC bags were stored at 25°C, 30°C, and 40°C. The solutions were investigated over 0, 1, 2, 3, 4, and 6 hours using HPLC analysis. The association between drug stability, temperature, and concentration was determined. Results The 5 mg/mL solutions of brand A and B imipenem mL were stable for 6 hours at 25°C, 30°C, and 40°C, respectively. For 10 mg/mL, the solution of brand A was stable for 3 hours and brand B was stable for 6 hours at 25°C. Also, brand A and B imipenem solutions at the concentration of 10 mg/mL were stable for less than 1 hour at 30°C and 40°C. Conclusion The stability of imipenem injection solution was affected by temperature and concentration. Increasing in temperature and drug concentration resulted in decreased stability of imipenem. Suitable temperature and drug concentration should be concerned when this drug is given by extended infusion.